ROLE OF SUCTION/INJECTION ON MIXED CONVECTION FLOW IN A VERTICAL MICROCHANNEL FILLED WITH POROUS MATERIAL - Daramola, Deborah A.; Ajibade, Abiodun O.; Lawal, Hammed. A. (FUDMA JOURNAL OF SCIENCES, 2023)
A suction/injection controlled mixed convection flow of an incompressible and viscous fluid in a vertical microchannel filled with porous material with asymmetric plate temperature is presented. The governing equations are derived and solved using the method of undetermined coefficient. The closed form expression for temperature field, velocity field, skin friction and Nusselt number for the steady fully developed flow are obtained analytically. The effects of the governing parameters on the microchannel hydrodynamic and thermal behaviors are determined. It is interesting to point out that growing the Darcy number as well as the suction S accelerate the fluid motion while they reduce the critical values of the  ( at which flow reversal sets in ) on both plates. The stability of the flow is affected by variation in the permeability of the porous material.
Keywords: vertical microchannel, mixed convection, temperature jump, velocity slip, porous media, suction, injection